LITERATURE REVIEW: RISK FACTORS FOR MALARIA INCIDENCE IN COASTAL AREAS - Febrinka, Najla; Shabrina, Dita; Sembiring, Mei Thalia; Syahfitri, Winda; Tumanggor, Winni R. E.; Naria, Evi (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2024)
Malaria is one of the vulnerable health problems experienced by residents in coastal areas. Therefore, this study attempted to examine malaria in coastal areas based on the epidemiological science approach and appropriate control strategies. The analysis technique used was literature review with articles collected from Science and Technology Index (SINTA) accredited journals or reputable international journals. The results obtained show that the incidence of malaria is influenced by several factors, including the use of mosquito nets and wire mesh, low education, the number of poor people, the percentage of slum households, the presence of breeding places, the habit of leaving the house at night, and the type of house walls. Suggestions that the government can appeal and educate the public about malaria can be done through community outreach programs, both on a national and international scale.